Rancang Bangun Aplikasi Game Edukasi Huruf, Angka Dan Gambar Pada Sekolah Mutiara Bagi Bangsa - Hermansyah, Pranata Yudistira; Setiawati , Popong (Jurnal Global Ilmiah, 2025)
Educational game applications have very high potential to increase motivation in the learning process. Apart from increasing motivation, educational games also have advantages compared to e-learning methods, they are easier to understand and more interesting. The design of this game will prioritize the teaching and learning process using the concept of "playing while learning". For some children, "learning" feels very unpleasant and boring, so by making educational games as interesting as possible, children will not realize that what they are doing is learning and children will enjoy the learning process. The method used in designing educational games for the Android-based Letter, Number and Picture Educational Game Application is System Development Life Cycle (SDLC) Waterfall and Unified Modeling Method Language (UML), this game was created with Android Studio software. It is estimated that this educational game can increase children's interest in learning.